Penerapan Kode Etik Jurnalistik Portal Fajar.Co.id dalam Pemberitaan COVID-19 - Misba, Misba; Safitri, Priska Nur (Mu'ashir: Jurnal Dakwah dan Komunikasi Islam, 2023)
This research is entitled the implementation of the Journalistic Code of Ethics (KEJ) on the Fajar.co.id portal in reporting on COVID-19. By using descriptive qualitative research type. Data collection methods are observation, interviews, and documentation. Interviews and documentation were conducted with Fajar.co.id editors, Fajar.co.id reporters Data analysis was carried out in three stages, namely data reduction, data presentation, and drawing conclusions. The results of this study indicate that Fajar.co.id journalists in reporting on Covid-19 are appropriate and apply a journalistic code of ethics. This is evidenced by the writing of the identity of the victim of the Covid-19 virus which was published with the permission of the patient himself. The researcher concludes that the implementation of the Journalistic Code of Ethics has objectively been carried out as it should be for Fajar.co.id media journalists, even though it is not optimal, but basically journalists are required to always carry out the demands of the Journalistic Code of Ethics, especially Article 2. This is evidenced by an attitude that has fulfilled the elements -Elements of the Journalistic Code of Ethics especially those contained in article 2. The Fajar.co.id leadership should also conduct periodic evaluations of journalists deployed in the regions. This is done to strengthen the journalists of the Fajar.co.id portal in carrying out the journalistic profession based on the applicable journalistic code of ethics